DICHOTIC LISTENING OF BILINGUAL CHILDREN AT INDONESIA INTERACTIVE STANDARD SCHOOL (IISS) MALANG - SOLIKHA, RIYADHATUS (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Dichotic listening, bilingual children, iDichotic Application, IISS Malang. Dichotic listening is a situation when two different auditory stimuli are presented simultaneously, one in each ear, to determine which syllable is perceived as being the clearest. There is a limited number of studies that have examined dichotic listening in Indonesia especially the performance of bilingual children. This study aims to investigate what is the dominant part and ear advantage of the participants and what factors (handedness, age, and fender) that may influence dichotic listening test result of bilingual children.Present study uses quantitative approach in order to produce clear and systematic description about the phenomena being studied. Descriptive analysis is applied in this study to describe dichotic listening test result of the participants. There are 45 right-handed bilingual children from IISS, Malang recruited as the participants. They consist of 25 boys and 20 girls, age 5-11 years old. The present study uses a tool named iDichotic application.This experiment has two main findings. The first finding shows most of bilingual children (88.9%) tend to perform right ear advantage (REA) dominantly and language stimuli are processed dominantly in the left hemisphere. The second finding is the factors that influence bilingual children dichotic listening test result are handedness factor with “very strong” correlation and gender factor with “strong” correlation. The age factor is not included because the result does not show a significant difference (“very low” correlation) since the participants are in the same age category which is Critical Period Hypotheses condition.The writer expects there will be more research conducted under dichotic listening topic, hence, the writer suggests the future research use more age variation of the participants and also the writer suggests to the Study Program of English to build a laboratory for dichotic listening research in order to make the students become interested in dichotic listening study.